Ted_Grendy
New member
- Joined
- Nov 11, 2018
- Messages
- 36
Hi All
I was wondering if someone could confirm if the following is correct:
I need to make Y the subject.
Ln(A)+n^2+1 = Ln(Y)
1) Because Ln(e) = 1
2) n^2 = (n^2)Ln(e) = Ln(e)^(n^2)
3) 1 = Ln(e)
4) Ln(A) + Ln(e)^(n^2) + Ln(e) = Ln(A * (e)^(n^2) * (e))
5) Ln(A * (e)^(n^2) * (e)) = Ln(Y)
6) A * (e)^(n^2) * (e) = Y
Thanks
I was wondering if someone could confirm if the following is correct:
I need to make Y the subject.
Ln(A)+n^2+1 = Ln(Y)
1) Because Ln(e) = 1
2) n^2 = (n^2)Ln(e) = Ln(e)^(n^2)
3) 1 = Ln(e)
4) Ln(A) + Ln(e)^(n^2) + Ln(e) = Ln(A * (e)^(n^2) * (e))
5) Ln(A * (e)^(n^2) * (e)) = Ln(Y)
6) A * (e)^(n^2) * (e) = Y
Thanks